2020
DOI: 10.3390/diagnostics10030130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Let-7 Family miRNA in Plasma as Potential Predictive Biomarkers of Diagnosis for Papillary Thyroid Cancer

Abstract: The most common histological type of thyroid cancer is papillary thyroid carcinoma (PTC). Radical resection of the thyroid gland is currently the recommended method of treatment. Almost 75% of thyroidectomies performed just for diagnostic purposes are benign. Thus, the confirmation of innovative and more precise noninvasive biomarkers holds promise for the detection of PTC, which may decrease the number of unnecessary thyroid lobectomies. In this work, using the droplet digital PCR (ddPCR) method, we have anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Comprehensively, a set of mi-RNAs (mi-RNA-375, 34a, 145b, 221, 222, 155, Let-7, and 181b) can be designated as a diagnostic biomarker to distinguish PTCs from benign nodules and identify cancer at an early stage [ 45 ]. Additional evidence suggests that plasma-derived mi-RNA-222 and another set of circulating mi-RNAs (let-7a, let-7c, let-7d, and let-7f) can be significantly increased in PTC patients compared to subjects with goiter or healthy controls [ 46 , 47 ]. In a prospective observational study, the serum levels of 754 mi-RNAs were measured in 11 PTC patients before and after surgery.…”
Section: Liquid Biopsy In Differentiated Thyroid Cancermentioning
confidence: 99%
“…Comprehensively, a set of mi-RNAs (mi-RNA-375, 34a, 145b, 221, 222, 155, Let-7, and 181b) can be designated as a diagnostic biomarker to distinguish PTCs from benign nodules and identify cancer at an early stage [ 45 ]. Additional evidence suggests that plasma-derived mi-RNA-222 and another set of circulating mi-RNAs (let-7a, let-7c, let-7d, and let-7f) can be significantly increased in PTC patients compared to subjects with goiter or healthy controls [ 46 , 47 ]. In a prospective observational study, the serum levels of 754 mi-RNAs were measured in 11 PTC patients before and after surgery.…”
Section: Liquid Biopsy In Differentiated Thyroid Cancermentioning
confidence: 99%
“…Furthermore, the study performed by Perdas et al suggested that the screening panel, consisting of four miRNAs, such as let-7a, let-7c, let-7d, and let-7f, whose levels were elevated in plasma, have a higher PTC screening utility [ 72 ]. Accordingly, Ricarte-Filho et al showed that the let-7 family affects growth and differentiation of PTCs.…”
Section: Ptc Screening Utility Of Selected Plasma and Serum Mirnasmentioning
confidence: 99%
“…The involvement of Let-7 in thyroid carcinogenesis has been described in a number of studies [ 18 ], however, all reports published thus far have focused on papillary thyroid cancer. For example, the elevated level of Let-7a, Let-7c, Let-7d, and Let-7f in the plasma of papillary thyroid cancer patients has been reported recently [ 19 ]. Moreover, Let-7 is being discussed as a promising serum for miRNA markers for the diagnosis and prognosis of thyroid cancer [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the Let-7 miRNA family, FTC-relevant miRNAs, other types of vesicular RNA, or other vesicular components can serve as a marker of follicular cell malignancy. Moreover, an increase in the plasma level of Let-7 miRNAs was also associated with papillary thyroid cancer [ 19 ]. These data and the design of our study do not allow us to argue about the diagnostic specificity of Let-7, even isolated from TPO(+)EV.…”
Section: Discussionmentioning
confidence: 99%